Quantcast
answersLogoWhite
notificationBell

Top Answer
User Avatar
Wiki User
Answered 2011-12-23 16:44:29

cos x - 0.5 = 0

⇒ cos x = 0.5

⇒ x = 2nπ ± π/3

001
๐Ÿ™๐Ÿฟ
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
๐Ÿ˜‚
0
User Avatar

Your Answer

Still Have Questions?

Related Questions

Determine exact solution for cosx minus 0.5 equals 0?

X=60 how did you get that? could you show all the steps?


What is the exact solution to cosx equals x?

There is no "exact" solution. This type of equation falls into the category of transcendental equations, which generally don't have exact solution except in special cases. The approximate solution, however, is roughly 0.739085


Prove this identity 1 plus cosx divide by sinx equals sinx divide by 1-cosx?

(1+cosx)/(sinx) = (sinx)/(1-cosx) (1+cosx)(1-cosx)/(sinx)(1-cosx) = (sinx)/(1-cosx) (1-(cosx)^2)/(sinx)(1-cosx) = (sinx)/(1-cosx) ((sinx)^2)/(sinx)(1-cosx) = (sinx)/(1-cosx) (sinx)/(1-cosx) = (sinx)/(1-cosx)


Can you Show 1 over sinx cosx - cosx over sinx equals tanx?

From the Pythagorean identity, sin2x = 1-cos2x. LHS = 1/(sinx cosx) - cosx/sinx LHS = 1/(sinx cosx) - (cosx/sinx)(cosx/cosx) LHS = 1/(sinx cosx) - cos2x/(sinx cosx) LHS = (1- cos2x)/(sinx cosx) LHS = sin2x /(sinx cosx) [from Pythagorean identity] LHS = sin2x /(sinx cosx) LHS = sinx/cosx LHS = tanx [by definition] RHS = tanx LHS = RHS and so the identity is proven. Q.E.D.


When does Cosx equals 1?

when the angle is 0 degrees


How would you find x when 0 equals 2sinxcosx-cosx?

2sinxcosx-cosx=0 Factored : cosx(2sinx-1)=0 2 solutions: cosx=0 or sinx=.5 For cosx=0, x=90 or 270 degrees For sinx=.5, x=30 degrees x = {30, 90, 270}


When are y equals sin x and y equals cos x equal?

y=sinx y=cosxsinx=cosx=>sinx/cosx=1=>tanx=1=>x=45oie.. y=sin45=cos45y=1/(square root of 2)


What is the period of y equals cosx?

The period is 2*pi radians.


How does secx plus 1 divided by cotx equal 1 plus sinx divided by cosx?

secx = 1/cosxand 1/cotx = tanx, therefore1/cosx + tanx = 1 + sinx/cosx, andsin/cos = tanx, therefore1/cosx + tanx = 1 + tanx, therefore1/cosx = 1, therfore1 = cosx.So, therfore, it is not neccesarily true.But if you meansecx plus 1 divided by cotx equals (1 plus sinx) divided by cosx(this is probably what you mean) Let's start over!secx = 1/cosxand 1/cotx = tanx, therefore1/cosx + tanx = (1+sinx)/cosx therefore1/cosx + tanx = 1/cosx + sinx/cosxsinx/cosx = tanx therfore1/cosx + tanx = 1/cosx + tanxDo you think this is correct? Subtract both sides by 1/cosx + tanx:0 = 0So, therefore, this is correct!(BTW, I'm in Grade 6! :P)


Does sin x tan x plus cos x equals tan x?

NO, sinxtanx=sinxsinx/cosx since tanx is sinx/cosx this is sin^2xcosx now add cosx cosx(sin^2x+1) after factoring Does this equal tanx? No, since this would require tanx to equal cosx(sin^2x+1) and it does not.


How do you simplify cosx plus sinx tanx?

to simplify Cosx=Sinx Tanx you should remember your fundamental and pythagorean identities.. Cosx + Sinx Tanx Cosx + Sinx (Sinx/Cosx) <---------- From Tanx= Sinx/Cosx Cosx + Sin2x/ Cos x <------------- do the LCD Cosx (Cosx/Cosx) + Sin2x/Cosx (Cos2x+Sin2x)/Cosx 1/Cosx <--------- From Sin2x + Cos2x =1 or Secx <-------- answer Comment if you have questions...:))


Is the solution of 1 plus cosx equals 0 is ฯ€ plus 2kฯ€?

Yes, that looks good. That's 180 degrees plus every multiple of 360 degrees more.


Cos x plus sin x equals 0?

cosx + sinx = 0 when sinx = -cosx. By dividing both sides by cosx you get: sinx/cosx = -1 tanx = -1 The values where tanx = -1 are 3pi/4, 7pi/4, etc. Those are equivalent to 135 degrees, 315 degrees, etc.



How do you solve 1 minus cosx divided by sinx plus sinx divided by 1 minus cosx to get 2cscx?

(1-cosx)/sinx + sinx/(1- cosx) = [(1 - cosx)*(1 - cosx) + sinx*sinx]/[sinx*(1-cosx)] = [1 - 2cosx + cos2x + sin2x]/[sinx*(1-cosx)] = [2 - 2cosx]/[sinx*(1-cosx)] = [2*(1-cosx)]/[sinx*(1-cosx)] = 2/sinx = 2cosecx


What are the solutions of 2 cos squared x minus cos x equals 1?

2cos2x - cosx -1 = 0 Factor: (2cosx + 1)(cosx - 1) = 0 cosx = {-.5, 1} x = {...0, 120, 240, 360,...} degrees


How do you prove the following equation the quantity of sin theta divided by 1 minus cos theta minus the quantity 1 plus cos theta divided by sin theta equals 0?

You will have to bear with the angle being represented by x because this browser will not allow characters from other alphabets!sin^2x + cos^2x = 1=> sin^2x = 1 - cos^x = (1 + cosx)(1 - cosx)Divide both sides by sinx (assuming that sinx is not zero).=> sinx = (1 + cosx)(1 - cosx)/sinxDivide both sides by (1 - cosx)=> sinx/(1 - cosx) = (1 + cosx)/sinx=> sinx/(1 - cosx) - (1 + cosx)/sinx = 0


How do you Prove sin x times sec x equals tan x?

sinx*secx ( secx= 1/cos ) sinx*(1/cosx) sinx/cosx=tanx tanx=tanx


How do you find the solutions of tanx equals 2cscx?

tanx=2cscx sinx/cosx=2/sinx sin2x/cosx=2 sin2x=2cosx 1-cos2x=2cosx 0=cos2x+2cosx-1 Quadratic formula: cosx=(-2±√(2^2+4))/2 cosx=(-2±√8)/2 cosx=(-2±2√2)/2 cosx=-1±√2 cosx=approximately -2.41 or approximately 0.41. Since the range of the cosine function is [-1,1], only approx. 0.41 works. So: cosx= approx. 0.41 Need calculator now (I went as far as I could without one!) x=approx 1.148


How do you solve sin squared x divided by 1 - cos x?

Use this identity sin2x+cos2x=1 sin2x=1-cos2x so sin2x/(1-cosx) =(1-cos2x)/(1-cosx) =(1-cosx)(1+cosx)/(1-cosx) =1+cosx


What is cosx times cosx?

It is cos2x that is, "cos-squared x".


What is the derivative of sin x minus cos x?

d/dx(sinx-cosx)=cosx--sinx=cosx+sinx


What is the derivative of x-cosx?

Take the derivative term by term. d/dx(X - cosX) = sin(X) ======


How do you prove the following identity sec x - cos x equals sin x tan x?

you need this identities to solve the problem..that is something you have to memorized sec x= 1/cosx 1-cos2x= sin2x tanx= sin x/cosx also, sin 2x= (sinx)(sinx) sec x - cosx= sin x tanx (1/cosx)-cosx= sin x tanx .. 1-cos2x / cosx=sin x tanx sin2x/ cosx= sin x tanx (sin x/cox)( sin x)= sin x tanx tanx sinx= sin x tanx


How do you break 1 sinx divided 1-cosx?

You may have a typo in your question. I'll answer it for sinx/(1-cosx) Multiply the numerator and denominator by (1 +cosx) and the denominator becomes (1-cos2x). By an identity, 1-cos2x = sin2x, giving you one term in the numerator. Your expression simplifies to sinx(1+cosx)/sin2x. Factor out sinx and you get (1+cosx)/sinx.


Still have questions?

Trending Questions
Previously Viewed
Unanswered Questions